A validated chiral chromatographic method for the enantiomeric separation of acalabrutinib. Issue 9 (21st June 2022) - Rayala, V. V. S. Prasanna Kumari; Trivedi, Kashyap Ajaybhai; Upadhyayula, Suryanarayana Murthy; Gunnam, Srinivasu; Borkar, Roshan M.; P, Radhakrishnanand
Abstract: Acalabrutinib is aided in the treatment of various cancers, which acts by inhibiting Bruton tyrosine kinase. Acalabrutinib belongs to the imidazopyrazine class consisting of a chiral carbon, resulting in two enantiomers. Currently, no methods exist for the separation and quantification of these enantiomers. A novel and selective enantiomeric chromatographic technique has been established to estimate the enantiomeric purity of acalabrutinib. Chiral separation was carried out on an immobilized amylose‐based chiral stationary phase with methyl tert ‐butyl ether/ethanol/ethylenediamine (60:40:0.1% v/v) mixture as a mobile phase. The total runtime is 20 min, and the resolution (Rs ) between the enantiomers was more than 2.5. The detection and quantification thresholds for the R‐enantiomer were 0.06 and 0.2 μg mL −1, respectively, for a test concentration of acalabrutinib (1000 μg mL −1 ). The linearity of the technique for the R‐enantiomer was excellent ( R 2  > 0.999) over the range from the limit of quantification to 0.3%. Recovery of the R‐enantiomer was ranged from 95% to 102%, indicating the greater accuracy of the technique. For a 48‐h research period, the drug was shown to be stable. Abstract :